Government Direction on the Vocational School’s Performance Evaluation in Indonesia and Malaysia: Some Notes from Islamic Education’s Perspective - Purwanto, Nurtanio Agus; Yuliana, Lia; Surya, Priadi; Suharyadi, Aris; Mat Nashir, Irdayanti; Abullah Kamal, Siti Soraya Lin; Darmadji, Ahmad (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
The vocational high school principal is a determining factor for the progress or failure of a school. Therefore, the principal's performance evaluation must be optimal. This study explores the government direction on this performance evaluation in two neighboring countries: Indonesia and Malaysia. The research method uses a qualitative approach, by interviewing both school supervisors and principals, and analyzing documents. The steps are 1) collection of resources through multi techniques; 2) reducing data with the aim of simplifying and categorizing data; 3) presenting data in the form of qualitative descriptions; 4) drawing conclusions and 5) compiling research reports and formulate comparative research findings. For Indonesia, once a year, the School Supervisor and a team from the Education Office in Indonesia are responsible for carrying out the review of the performance of the principals of vocational schools. The current evaluation of the principal of a vocational high school in Malaysia is a component of the overall review of the school's performance. Standard of Educational Quality in Malaysia is the name given to this evaluation, and it has been in effect since 2017. Standard 1 Kepemimpin is the most important benchmark to consider in relation to principal performance (Leadership). The performance evaluation in Indonesia seems still separated from school performance evaluation or accreditation. Although each evaluation scheme has its own format and purposes, the implementation could be made in such a concurrent time. Meanwhile in Malaysia, the principal performance is likely one of the evaluated aspects in the school performance evaluation (SKPM), especially Standard 1 Kepemimpinan (leadership) and Standard 2 Pengurusan Organisasi (organization management).